A new species of the genus Hyidiothrips (Thysanoptera: Phlaeothripidae) from China - Wang, Jun; Tong, Xiao-Li; Zhang, Wei-Qiu (Zootaxa, 2006)
Hyidiothrips guangdongensis sp. n., a new species of the subfamily Phlaeothripinae (Thysanoptera, Phlaeothripidae) is described from China. The new species is similar to Hyidiothrips japonicus Okajima, but can be distinguished from the latter by the following features: pronotum longer than head; antennal segment I brown, segment II yellowish and segments III–VII dark brown; median sclerite of pelta blunt posteriorly, separated from anterior sclerite, posterior sclerite distinctly divided into two lateral plates in female. The type specimens are deposited at the Insect Collection, Department of Entomology, South China Agricultural University.